Antiplatelets and Anticoagulants in Vitreoretinal Surgery: A Systematic Review - Filippo Confalonieri; Vanessa Ferraro; Alessandra Di Maria; Alessandro Gaeta; Josè Luis Vallejo-Garcia; Paolo Vinciguerra; Xhevat Lumi; Goran Petrovski (Life, 2023)
Background: Antiplatelets and anticoagulants have substantially influenced contemporary vitreoretinal surgical practices. The availability of new oral blood thinners has recently spurred a renewed interest in the clinical approach to vitreoretinal surgical conditions since it may be difficult for the surgeon to collect sufficient evidence-based data to decide whether to discontinue or continue such medications. Materials and Methods: We conducted a systematic review on the use of antiplatelets and/or anticoagulants in the perioperative setting in vitreoretinal surgery and their possible complications, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The level of evidence, according to the Oxford Centre for Evidence-Based Medicine (OCEM) 2011 guidelines, and the quality of evidence, according to the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system, were assessed for all included articles. Results: In total, 2310 articles were initially extracted, out of which 1839 articles were obtained after duplicates were removed and their abstracts were screened. A total of 27 articles were included in the full-text review. Finally, a remaining 22 articles fulfilled the inclusion criteria. Conclusions: Even though there is just a small number of studies with solid results, the advantage of using antiplatelets and/or anticoagulants in vitreoretinal surgery seems to outweigh the disadvantages, which are mainly related to postoperative hemorrhagic complications.